Does customers' attitude toward negative eWOM affect their panic buying activity in purchasing products? Customers satisfaction during COVID-19 pandemic in Indonesia - Elia Ardyan; Daniel Kurniawan; Istiatin Istiatin; Luhgiatno Luhgiatno (Cogent Business & Management, 2021)
Concerning the effect of the 2019 coronavirus novel (COVID-19) pandemic on the global economic situation, this study examines the impact of customer attitudes toward negative Electronic Word of Mouth (eWOM) in their panic buying activities and switching barriers on customer satisfaction. This study also used the Rational Choice Theory approach as a foundation to explain the current situation in Indonesia regarding customer purchasing decisions and satisfaction. The questionnaires were distributed online to 691 consumers in various cities in Indonesia. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results of this study indicate that the attitudes toward negative eWOM have an impact on increasing panic buying activity and brand switching. Finally, the relationship between buying activity as well as brand switching toward customer satisfaction has significance. The conclusions drawn in this study will contribute to studies or research regarding Rational Choice Theory.
Keywords: 650; COVID-19; attitudes toward negative eWOM; customer panic buying activity; brand switching; customer satisfaction